Analisa Prioritas Penanganan Pemeliharaan Jalan Menggunakan Program Provincial/ Kabupaten Road Managemen System (P/KRMS) Pada Ruas Jalan 106.1 Jalan Batu Maali-RSUD Dan 106.2 Jalan Batu Maali-RSUD - Haryati, Nina; Anafi S, La Ode (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Roads are part of the national transportation system, Analysis of current road handling priorities The Directorate General of Highways, Ministry of PUPR has issued a guide in the form of a computer-based application/program called P/KRMS which is an abbreviation of (Provincial/Regency Road Management System) which has features related to road handling priorities. The Provincial/Regency Road Management System (P/KRMS) application aims to analyze data to determine existing damage based on the type of damage level and its causative factors so that the results of road handling priorities are obtained based on the damage and its causes. This study aims to analyze road maintenance handling priorities using the Provincial/Regency Road Management System (P/KRMS) application and to determine the level of road damage on 2 road sections in Baubau City in terms of condition and inventory. This study takes data directly from the field, which includes measurements, types of pavement damage, types of pavement used and traffic data. Based on the results of the survey, the Batu Maali-RSUD road is in a state of severe disrepair, with damage reaching 85% of the total length of the road. Meanwhile, the road is in moderate condition with damage reaching 9%, and the road is in good condition with damage reaching 6%. The total length of the road section, according to the Baubau City Road Decree, is 3.313 km. The condition of the two sections of the Batu Maali-RSUD road in Baubau City is in a state of severe disrepair, requiring routine maintenance, periodic maintenance, and structural improvements.